The Relationship of Learning Independence with Learning Outcomes of Pactical Office Advance Training Participants at BLK Lubuk Sikaping - Shafira Aulia Miranda; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This research was motivated by the low learning outcomes of trainees in the pratical office advance program at BLK Attitude, which was allegedly due to the low learning independence of trainees in the pratical office advance program at BLK Attitude. This study aims to reveal a description of the relationship between learning independence and learning outcomes in the practical office advance program at BLK Attitude. This study uses a quantitative approach with a correlational type. The population in this study were all 32 participants of the second wave of practical office advance training for the 2022 period. While the sample was taken using simple random sampling as many as 75% as many as 24 people. Data collection techniques using a questionnaire. The data analysis technique uses the rank order correlation formula. The results showed that: 1) the learning independence of the trainees in the practical office advance program at BLK Attitude was still low; 2) the learning outcomes of the practical office advance program training participants are still low; 3) there is a significant relationship between learning independence and learning outcomes in the practical office advance program at BLK Attitude